(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
This study intends to offer a planned overview of source systems for academics and management interested in the subject. It does not try to provide a complete overview of the vast and rapidly expanding review , but it does show the range and depth of study and practice in the field. The paper’s main point is that the spectrum can be interpreted from four different perspectives, which all researchers and professionals use explicitly or implicitly: surface water, as a buyer; downstream, as a seller; static network, as an accountant of position inside its own supply chain network, largest service several supplier relationships, offering a stationary and relative view; and dynamic network, as a manager.